Causal effects from non‐alcoholic fatty liver disease on kidney function: A Mendelian randomization study. (7th December 2021) - Park, Sehoon; Lee, Soojin; Kim, Yaerim; Cho, Semin; Kim, Kwangsoo; Chul Kim, Yong; Han, Seung Seok; Lee, Hajeong; Lee, Jung Pyo; Joo, Kwon Wook; Lim, Chun Soo; Kim, Yon Su; et al.
Abstract: Background and aims: An observational association between nonalcoholic fatty liver disease (NAFLD) and kidney function impairment has been reported. We aimed to investigate the causal effects from NAFLD on estimated glomerular filtration rate (eGFR) by a Mendelian randomization (MR) study. Methods: We first performed single‐variant MR with rs738409 as a genetic instrument for NAFLD. Another genetic instrument was developed from a genome‐wide association study for biopsy‐confirmed NAFLD among individuals of European ancestry (1483 cases and 17 781 controls). The eGFR outcome was assessed in individuals of white British ancestry from the UK Biobank (N = 321 405). The associations were reassessed in the negative control subgroup (body mass index < 30 kg/m 2, absence of central obesity, and serum alanine aminotransferase level ≤ 20 IU/mL) with a low probability of developing NAFLD. As a replication analysis, a summary‐level MR was performed with the European ancestry CKDGen dataset (N = 567 460). Results: In the UK Biobank, a genetic predisposition for NAFLD, determined either by the single SNP rs738409 or by the group of variants, was significantly associated with a reduced eGFR even with adjustment for metabolic disorders. Although the associations were not significant in the negative control subgroup with a low probability of developing NAFLD, they were significant in the subgroup with a remaining risk of NAFLD, suggesting the absence of a horizontal pleiotropic pathway. The summary‐level MR from the CKDGen dataset supported the causal effects of NAFLD on reduced eGFR. Conclusions: This MR analysis supports the causal reduction in kidney function by NAFLD.